A Comparative SEM-EDX Study on the Enamel Remineralization Potential of Bioactive Glass 45S5 and Nanohydroxyapatite in a Novel Orthodontic Adhesive Used to Bond Orthodontic Brackets on Bovine Teeth/Marie Carmina Gulmatico-Dela Cruz. - Gulmatico-Dela Cruz, Marie Carmina
Enamel demineralization, often manifesting as white spot lesions, affects approximately 96% of patients undergoing fixed orthodontic treatment.
Traditionally, fluoride has been the primary agent for enamel remineralization; however, recent advancements have highlighted the effectiveness of bioceramics,particularly bioactive glass 45S5 (BAG) and nanohydroxyapatite (NHAp). This study explores a novel approach by incorporating bioceramics into a commercially-available flowable composite to create a remineralizing orthodontic bracket adhesive resin cement. Sixty bovine teeth were prepared and assigned to five groups: baseline, 3M Transbond XTTM, GC Fuji Ortho LCTM, 15% BAG, and 10% NHAp. Each tooth was bonded with an orthodontic bracket using the respective cement. The samples underwent a 9-day pH cycling regimen, following the Toda and Featherstone protocol. Qualitative and quantitative assessment of enamel remineralization was performed using Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDX).
Results indicated a decline in Ca/P ratios post-demineralization across all groups, with GC Fuji Ortho LCTM showing the smallest reduction (0.29, p =0.0002). In contrast, 15% BAG exhibited the largest decline (1.11, p = 0.0001). Although there was a statistically significant increase in Ca/P ratio for the 15%BAG group post-pH cycling (-0.01, p = 0.0001), it remained significantly lower than baseline (1.103, p = 0.0001), indicating limited remineralization capability.
Conversely, the 10% NHAp group demonstrated the most significant increase in Ca/P ratio post pH-cycling (-0.27, p = 0.0001) and no significant difference compared to baseline (-0.05, p = 1.0000), highlighting its superior ability to remineralize enamel. SEM imaging revealed the formation of an apatite-like layer on enamel treated with 10% NHAp, suggesting its potential for enhanced enamel protection and ion reservoir properties.
This study underscores the potential of 10% nanohydroxyapatite as an effective agent for enamel remineralization in orthodontic applications, offering promising benefits over traditional and other bioceramic options.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Dental enamel; Orthodontics